Effect of Feeding Various Sources of Zinc on Nutrient Digestibility and Rumen Parameters of Male Crossbred Calves - Kachhadia, Laxit; Katole, Shrikant B; Pandya, Paresh R.; Sorathiya , Kalpesh (Indian Journal of Animal Nutrition, 2023)
This study was conducted to investigate the effect of replacing inorganic zinc with lower level of organic and nano zinc on digestibility of nutrients and rumen parameters of growing crossbred calves. For this experiment, 15 male crossbred calves weighing 93.39±3.19 kg (8-10 months) were divided into three groups consisting of five animals in each. TMR having 50:50 roughage to concentrate ratio with 2 kg of green fodder was provided to animals as a basal diet. Along with basal diet experimental groups were provided with additional Zn sources i.e., ZnSO4 (@40 ppm) in T1, Zn-glycinate (@20 ppm) in T2 and nano ZnO (@10 ppm) in T3, for the period of 98 days. Digestibility of nutrients like DM, OM, CP, EE, CF, NFE, NDF and ADF was comparable (P>0.05) among the group. Various rumen parameters like ruminal pH, TVFA, ammonia-N, total-N, non-protein and soluble nitrogen concentration was also comparable (P>0.05) among the groups. However, periodical changes were observed between different time intervals. It may be concluded that, supplementation of nano ZnO (@10 ppm), Zn-glycinate (@20 ppm) and ZnSO4 (@40 ppm) gave comparable (P>0.05) results on growing crossbred calves without any adverse effect.